2021
DOI: 10.21037/apm-20-2281
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of the dural puncture epidural technique combined with programmed intermittent epidural boluses for labor analgesia

Abstract: Background: Continuous epidural infusion (CEI) can provide analgesia during labor. The dural puncture epidural (DPE) technique is used to accelerate the onset of neuraxia anesthesia. The primary objective of this study was to compare the percentage of patients that received adequate labor analgesia following an injection of 0.08% epidural ropivacaine via the DPE and CEI techniques combined with the PIEB mode of maintenance.Methods: Patients who were laboring were randomly allocated to receive either CEI + PIEB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 19 publications
1
36
1
Order By: Relevance
“…Although the motor block degree reported by previous studies was comparable between the DPE and EA techniques for labor analgesia [ 15 , 18 , 24 ], the DPE technique resulted in significantly higher motor block scores at each time point than the EA technique in our study. One possible reason is that the concentration of local anesthetics was significantly higher than that in other studies applied for labor analgesia, in which a low concentration of ropivacaine produced motor-sensory separation.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Although the motor block degree reported by previous studies was comparable between the DPE and EA techniques for labor analgesia [ 15 , 18 , 24 ], the DPE technique resulted in significantly higher motor block scores at each time point than the EA technique in our study. One possible reason is that the concentration of local anesthetics was significantly higher than that in other studies applied for labor analgesia, in which a low concentration of ropivacaine produced motor-sensory separation.…”
Section: Discussioncontrasting
confidence: 69%
“…As early as 1998, Leach et al [ 23 ] observed the translocation of epidural dye into the subarachnoid space through an accidental dural puncture via a tuohy needle (gauge not documented), which verified the theory. Previous studies have shown that the DPE technique using a 25-G or 26-G Whitacre needle resulted in earlier and greater sacral spread than the EA technique[ 12 , 13 , 24 ]. In addition, an in vitro study demonstrated notable lidocaine flux into the subarachnoid space via an 18-G or 24-G needle puncture but no flux via a 27-G needle puncture[ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e high rate of cesarean section has become not only a medical problem faced by the medical profession but also a serious "public health problem" faced by our country. Among the social factors of cesarean section, maternal inability to bear labor pain is the first cause [19]. In addition, some studies have indicated that labor analgesia can reduce the rate of cesarean section, so the promotion of labor analgesia has important social significance to change the current situation of high cesarean section rate in China [20].…”
Section: Discussionmentioning
confidence: 99%
“…7 Other groups found no or minimal differences between dural puncture epidural and conventional epidural blocks, and two meta-analyses published in 2019 concluded the differences were minor at best. 8,9 Subsequently, published studies from several international groups once again found slightly faster onset of adequate analgesia with dural puncture epidural, 10–12 but other studies found trivial or no differences. 13 While it is unclear why such disparate results have been observed, variations in spinal needle size, epidural drug administered, patient population studied, method of analgesia assessment, and other unknown confounders or random variation may be responsible.…”
mentioning
confidence: 99%